Theological Values Internalization in Central Learning Management at Kindergarten - Ningsih, Tutuk; Ardy Wiyani, Novan (Edukasia Islamika : Jurnal Pendidikan Islam, 2021)
This qualitative research is intended to describe the internalization of theological values in the management of learning centers in kindergarten al-Irsyad al-Islamiyyah Purwokerto. The data were collected using interview, observation, and documentation techniques and then analyzed using the Miles and Huberman data analysis technique. The results shows that the internalization of theological values in the management of learning centrals was carried out through five attempts. The first attempt is the internalization of theological value into the vision and quality assurance of graduates. The second is the internalization of theological values by organizing ritual centers. The third is the internalization of theological values by integrating religion and science into learning themes. The fourth is the internalization of theological values through habituation activities. The fifth is the internalization of theological value through the activities of telling stories about the Prophet as well as the Companions of the Prophet. The implication of doing this research is to provide descriptions to other researchers to examine the early children education curriculum that is able to integrate religion and science in thematic learning using a center approach.